1999
DOI: 10.1055/s-2007-971125
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characteristics of Well-Trained Synchronized Swimmers in Relation to Performance Scores

Abstract: The purpose of this study was to examine the relationships between the physiological characteristics of synchronized swimmers and their performance scores. The subjects were 16 trained female synchronized swimmers with a mean age of 17.2 +/- 1.7 years (mean +/- SD). The examined variables were body dimensions (height, width, body mass, circumference of the body and segment length), body composition, isokinetic muscle strength of the elbow and knee during extension and flexion, abdominal muscle endurance, anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…According to a few studies, lower limb muscle strength is quielty important especially in sprint swimming performance (Yamamura et al, 1999). In the present study, there was a strong relationship between 25-m swimming performance and lower limb musle strength and these findings are in line with literature (Yamamura et al, 1999;.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to a few studies, lower limb muscle strength is quielty important especially in sprint swimming performance (Yamamura et al, 1999). In the present study, there was a strong relationship between 25-m swimming performance and lower limb musle strength and these findings are in line with literature (Yamamura et al, 1999;.…”
Section: Discussionsupporting
confidence: 92%
“…suggested that swimming sport requires high muscle power in lower limb. Similarly, a study conducted with synchronized swimmers, found that there is a strong correlation between performance and isokinetic muscle strength of the lower limb muscle (Yamamura et al, 1999). On the other hand, Gola et al (2014) reported that there is no relationship between isometric strength of the lower limb muscles and 25-m or 50-m swimming performance.…”
Section: Introductionmentioning
confidence: 94%
“…Other physiological findings include those from Yamamura et al (1999), who found a significant correlation between aerobic capacity and synchronized swimming performance scores. They also noted a correlation between performance scores and isokinetic muscle strength of elbow extension and flexion, knee extension, abdominal muscle endurance, leg extension power, and swimming velocity at the onset of blood lactate accumulation.…”
Section: Physiological Requirements Of the Sportmentioning
confidence: 97%
“…However, in a more recent investigation, the mean aerobic power of the Japanese national team (tested in a swimming flume) was higher (50.8 (2.9) ml/kg/min). 25 Although it is diYcult to examine the eVect of training on menstrual function in isolation, it remains to be seen whether an increase in the aerobic training intensity of the current cohort of synchronised swimmers would lead to an increased incidence of menstrual irregularity. This study suggests that elite level synchronised swimmers in the United Kingdom are not at risk of developing menstrual abnormalities and consequently are unlikely to have reduced bone mineral density.…”
Section: Discussionmentioning
confidence: 99%